NLRP2 Regulates Proinflammatory and Antiapoptotic Responses in Proximal Tubular Epithelial Cells - Rossi, Marianna N.; Pascarella, Antonia; Licursi, Valerio; Caiello, Ivan; Taranta, Anna; Rega, Laura R.; Levtchenko, Elena; Emma, Francesco; De Benedetti, Fabrizio; Prencipe, Giusi (Frontiers in Cell and Developmental Biology, 2019)
Nod-like Receptor Pyrin domain containing proteins (NLRPs) expressed by resident renal cells may contribute to the pathogenesis of multiple renal diseases. Cystinosis is a genetic disorder that affects kidney and particularly proximal tubular epithelial cells (PTEC). Here, we investigated the expression of NLRP family members in human control and cystinotic conditionally immortalized PTEC. Among all the NLRPs tested, we found that NLRP2 is highly expressed in cystinostic PTEC, but not in PTEC from healthy subjects. The NLRP2 overexpression was confirmed in primary PTEC and in kidney biopsies from cystinotic patients. In order to elucidate the role of NLRP2 in PTEC, we stably transfected control PTEC with an NLRP2-containing plasmid. We showed that NLRP2 markedly increases the production of several NF-kB regulated cytokines and chemokines. Accordingly, we demonstrated that NLRP2 interacts with IKKa and positively regulates the DNA-binding activity of p50 and p65 NF-kB, by modulating the p65 NF-kB phosphorylation status in Serine 536. Transcriptome analysis revealed that NLRP2 also upregulates the expression of profibrotic mediators and reduces that of several interferon-inducible genes. Finally, NLRP2 overexpression decreased the apoptotic cell rate. Consistently, silencing of NLRP2 by small-interfering RNA in cystinotic PTEC resulted in a significant decrease in cytokine and chemokine production as well as in an increase in the apoptosis rate. Altogether, our data reveals a previously unrecognized role for NLRP2 in regulating proinflammatory, profibrotic and antiapoptotic responses in PTEC, through NF-kB activation. Moreover, our findings unveil a novel potential mechanism involving NLRP2 overexpression in the pathogenesis of cystinosis.